2009
DOI: 10.1063/1.3079502
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of electronic and optical characteristics of n-GaN-based structures by photoelectrochemical oxidation in glycol solution

Abstract: Surface control of n-GaN was performed by applying a photoelectrochemical oxidation method in a glycol solution to improve the optical and electronic characteristics. The fundamental properties of the oxidation were investigated. The oxidation, chemical composition, and bonding states were analyzed by x-ray photoelectron spectroscopy and micro-Auger electron spectroscopy, in which confirmed the formation of gallium oxide on the surface. The oxide formation rate was about 8 nm/min under UV illumination of 4 mW/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The insert in Figure shows O 1s and Ga 3d XPS spectra. The O 1s peak at 531.3 eV is attributed to chemisorbed oxygen and the Ga 3d core level yields peak positions at 20.6 to 20.8 eV for Ga–O bonding and 19.6 to 19.8 eV for Ga–N bonding. , Therefore, the Ga 3d peak at 19.8 eV can be assigned to nitride. The O 1s and Ga 3d peaks confirm that the samples are gallium nitride and not oxide.…”
Section: Resultsmentioning
confidence: 99%
“…The insert in Figure shows O 1s and Ga 3d XPS spectra. The O 1s peak at 531.3 eV is attributed to chemisorbed oxygen and the Ga 3d core level yields peak positions at 20.6 to 20.8 eV for Ga–O bonding and 19.6 to 19.8 eV for Ga–N bonding. , Therefore, the Ga 3d peak at 19.8 eV can be assigned to nitride. The O 1s and Ga 3d peaks confirm that the samples are gallium nitride and not oxide.…”
Section: Resultsmentioning
confidence: 99%
“…28 The broader linewidth and the chemical shift of Ga Auger signal were also observed in the GaO x layer prepared by photoelectrochemical oxidation of GaN. 29 That is, the XPS spectra obtained from the N 2 O-radical treated surface contain those of the AlGaN and AlGa-oxide layers, suggesting the oxidation layer was very thin (1 nm or less). Bae et al 30 reported that an ultra thin Ga-oxide layer prepared by the remote plasma-assisted oxidation process is effective in reducing interface states for the SiO 2 /n-GaN system.…”
Section: B Chemical Properties Of N 2 O-radical Treated Algan Surfacementioning
confidence: 99%
“…Fig. 7 compares the O 1s core-level spectra of the HPWV-annealed and reference samples taken with a photoelectron escape angle of 45°, corresponding to a probing depth of 2-3 nm [19]. It should be noted that XPS profiles were calibrated to the adventitious C 1s peak position [20] and then normalized to their respective N 1s peak intensities.…”
Section: Device Characteristics and Discussionmentioning
confidence: 99%